Incidence of Highly Pathogenic Avian Influenza H5N1 in Nigeria, 2005–2008. Issue 3 (25th April 2012) - Henning, J.; Bett, B.; Okike, I.; Abdu, P.; Perry, B.
Summary Outbreaks of highly pathogenic avian influenza (HPAI) H5N1 occurred in Nigeria between December 2005 and July 2008. We describe temporal and spatial characteristics of these outbreaks at State and Local Government Area (LGA) levels. A total of 25 of 37 States (67.6%; Exact 95% CI: 50.2–82.0%) and 81 of 774 LGAs (10.5%; Exact 95% CI: 8.4–12.8%) were affected by HPAI outbreaks over the period from 2005 to 2008. The incidence risk of HPAI outbreak occurrence at the State level was 5.6% (0.7–18.7%) for 2005, 50.0% (30.7–69.4%) for 2006, 54.5% (29.9–80.3%) for 2007 and 0% for 2008. Only very few LGAs experienced HPAI outbreaks within the affected States. The incidence risk of HPAI outbreak occurrence on a LGA level was 0.3% (0.0–0.9%) for 2005, 6.6% (4.9–8.6%) for 2006, 4.2% (2.9–6.0%) for 2007 and 0% for 2008. The mean period between farmers noticing HPAI outbreaks and reporting them to veterinary authorities, and between reporting HPAI outbreaks and the depopulation of infected premises, was for both 4.5 days; both periods also had medians of 1 day. We have estimated the spatially smoothed incidence risk for the whole outbreak period and identified the existence of a large corridor in the western part of Nigeria and a smaller corridor in south‐eastern part, where the risk of HPAI occurrence was lower than in the rest of the country. The effect of HPAI control policies on the outbreaks patterns are discussed, as well as possible reasons why HPAI did not become endemic in Nigeria.